The male embarrassment: nudism and the fear of erections. - Allan, Jonathan A. (Journal of Gender Studies, 2026)
Nudism is a social practice wherein people are naked together. At its core, nudism holds that being naked is not inherently sexual; that is, the naked body is natural and instead is made sexual. What, then, might an erection mean or signify at the nudist resort of camp? What happens if a man has an erection? This article explores discussions of the erection in nudist publications. I show how nudist writings address the fear of erection by holding on to the principle that nudism is not sexual and, second, that should an erection arise, readers are provided with helpful hints and tips about what to do. The erection presents a unique challenge to nudism because the erection, like nudism, is neither inherently nor essentially sexual and instead can be a physiological reaction. While many publications debated nudism and erections, only one publisher dared to challenge the pictorial conventions and opted to publish the erect penis. I argue that in so doing, this publisher challenged the norms of nudist ethics but also ultimately contributed to the downfall of nudist magazines.